Survey on the Status of Business Women in Mozambique - Serra, Andrea (International Finance Corporation, Washington, DC, 2017)
This report presents the results of a study which aims to ascertain the status of and challenges facing Mozambican women's small and medium enterprises (SME´s). The study was carried out through a quantitative survey and focus group discussions among a convenience sample of 70 business women, from which 19 of them were Mozambican Association of business and executive woman (ACTIVA's) members and 59 were potential members. The study will collect elements that will allow a better knowledge of the entrepreneurial capacity of ACTIVA members and potential members, their training needs and technical backup as well as support for their business development. The survey will therefore be essential for ACTIVA and will provide information for the International Finance Corporation (IFC) on needs to anticipate support strategies on behalf of potential members of the association. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.